Ultra-low-energy (<10 eV/u) ion beam bombardment effect on naked DNA - P. Thopan (2018)
Since ion energy deposition in the ion-bombarded materials dominantly occurs in the low-energy range, it is very interesting to know effects from ultra-low-energy ion interaction with DNA for understanding ion-beam-induced genetic mutation. Tens-keV Ar- and N-ion beams were decelerated to ultra-low energy ranging from 20 to 100 eV, or only a few to 10 eV/u, to bombard naked plasmid DNA. The bombarded DNA was analyzed using gel electrophoresis for DNA form changes. The original DNA supercoiled form was found to change to relaxed and linear forms, indicating single or double strand breaks after bombarded by tens-eV ion beam. N-ion beam was found more effective in inducing DNA change and mutation than Ar-ion beam. The study demonstrated that the ion bombardment with energy as low as several-tens eV was able to break DNA strands and thus potentially to cause genetic modification of biological cells. The experimental results were discussed in terms of direct atomic collision between the ions and DNA atoms. © 2014 Elsevier B.V. All rights reserved.